Comparison of cosmetic outcomes between remote‐access and conventional thyroidectomy: A review of the current literature. Issue 1 (18th April 2022) - Kasouli, Anna; Spartalis, Eleftherios; Giannakodimos, Alexios; Tsourouflis, Gerasimos; Dimitroulis, Dimitrios; Nikiteas, Nikolaos I.
Abstract: Objective: The pursuit of an esthetically pleasing scar following open thyroid surgery has led to the development of endoscopic thyroidectomy through remote incisions placed in several locations outside the neck. The objective of this study is to review the recent literature and compare the incision site appearance and patient satisfaction with the cosmetic outcome after extracervical and conventional thyroidectomy. Methods: The English literature published since 2010 was searched through the PubMed/Medline database for studies comparing the cosmetic outcomes between remote‐access endoscopic and conventional thyroidectomy using a form of scar assessment scale. Results: A total of 9 relevant papers fulfilled the eligibility criteria including 1486 patients. Among them, 595 patients underwent endoscopic thyroidectomy through several remote‐access approaches and 891 patients were assigned to the conventional group. Only one randomized‐controlled trial was identified, whereas among the rest, four were prospective and four were retrospective nonrandomized cohorts. Regarding the extracervical modifications performed in the endoscopic groups, the axillary approach was performed in three studies and the breast approach in four studies, while the retroauricular facelift technique and the transoral vestibular method were applied in one study, respectively. Conclusions: Evaluation of the wound appearance and patient satisfaction with the cosmetic outcome at various time points during the follow‐up highlighted the superiority of the extracervical approaches over the conventional cervicotomy. Considering these findings, remote‐access techniques could possibly be the ideal surgical method for patients with high esthetic requirements, providing an excellent appearance of the thoroughly exposed neck. Key points: Conventional open thyroidectomy is considered the gold standard approach for thyroid diseases. Endoscopic thyroidectomy through extracervical incisions provided a scarless appearance of the neck and greater patient satisfaction with the cosmetic outcome. Abstract : Increased expectations in terms of cosmetic outcomes have led to the evolution of endoscopic extracervical thyroidectomy. These remote‐access techniques led to greater cosmetic satisfaction among patients, providing a scarless appearance of the neck.